A aglomeração urbana de Piracicaba: uma análise da integração funcional entre os municípios sob a ótica do movimento pendular - Corrêa, Daiana Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The growth area of cities has resulted in a phenomenon of conurbation (or expressing tendency). This correspond to a combine of two or more urban cores, there are formations of conurbations. In this way, there are the formations of urban concentrations and can achieve the step metropolitan or not metropolitan. Besides, this kind of expansion generates many social and environmental problems related about habitation, rubbish, drain, and others. Piracicaba, a city in expansion, recently, shows evidences of conurbation not metropolitan around itself. Like this, the paulista government, at June, 26 of 2012, institutionalized the Urban Concentration of Piracicaba, a regional unity, intending the administration along with 22 cities. However, for this fact, must be taken into account functional integration among urban centers, because the number of municipalities are presented to compose a urban concentration of level not metropolitan. It has checked along this research, according with proposition about 22 cities. Thus, the objective of this research is identify and analyze the functional integration among participating municipalities through the commuting, in other words, the spatial displacement of people, important factor to be taken into account when defining urban concentration. Considering the displacement routine people, the commuting, also aimed identify the flow of public transport intercity travel among the cities of Piracicaba Regional Unity. Then, analyze the criteria used for establish the Piracicaba Regional Unity, if it was considered technical character or if it was prioritized the political character. To conduct this research, it was done the literature review related to the theme and data collection related lines of intercity transportation and often travel with ARTESP and companies responsible for it service

O crescimento acelerado das cidades tem resultado no fenômeno de conurbação (ou manifestando tendência para), o qual corresponde a junção de dois ou mais núcleos urbanos. Como consequência desse processo, tem-se a formação das aglomerações urbanas que podem atingir a escala metropolitana ou não. Além disso, esse tipo de crescimento acarreta em diversos problemas socioambientais relacionados à moradia, lixo, esgoto, entre outros. Piracicaba, cidade em franca expansão, recentemente, apresenta indícios da formação de uma aglomeração urbana não metropolitana ao seu entorno. Desta forma, o governo estadual paulista, em 26 de junho de 2012, institucionalizou a Aglomeração Urbana de Piracicaba como Unidade Regional, visando a administração conjunta entre os 22 municípios participantes. Todavia, para tal fato deve ser levada em consideração a integração funcional entre os núcleos urbanos, visto que tal número de municípios apresenta-se elevado para compor uma aglomeração urbana de nível não metropolitano. É o que se verifica no decorrer deste trabalho com cada núcleo urbano, de acordo com a proposta de 22 municípios. Deste modo, o objetivo deste trabalho é identificar e analisar a integração funcional entre os municípios participantes por meio do movimento pendular, ou seja, o deslocamento espacial de pessoas, fator importante a ser levado em consideração ao se definir aglomerações urbanas. Como se considerou o deslocamento rotineiro de pessoas, o movimento pendular, também se objetivou identificar o fluxo de viagens do transporte coletivo intermunicipal entre as cidades da AU de Piracicaba, podendo então analisar quais os critérios utilizados para a instituição da Aglomeração Urbana de Piracicaba, se foi levado em consideração o caráter técnico ou se foi priorizado o caráter político... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Aglomeração Urbana de Piracicaba (SP : Microrregião); Geografia urbana; Integração funcional; Transportes coletivos; Piracicaba (SP) - Geografia